The Role of Clinical Research In Combatting NCD - Ngah, Nor Fariza (International Journal of Human and Health Sciences (IJHHS), 2024)
Clinical trials are a powerful tool in addressing the global health challenge posed by Non- Communicable Diseases (NCDs) like cardiovascular disease, diabetes, cancer, and many more. They have played a pivotal role in shaping our understanding and combating NCDs, contributing to significant progress in prevention, diagnosis, and treatment strategies and unmet needs. Key impacts of clinical trials in the realm of NCDs include precision medicine, early detection, treatment advancement, preventive strategies, health equity, data and evidence generation, and patient empowerment. While the journey to combat NCDs has been long and challenging, the progress achieved through clinical trials has proven to be truly motivating. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S6